Critical aesthetics and postmodernism - Crowther, Paul 1953- (Clarendon Press, 1993)
In recent times considerable controversy has raged around the question of postmodern culture and its products. Paul Crowther attempts to overcome some of the antagonistic viewpoints involved by expounding and developing key themes from the work of Kant and Merleau-Ponty in the context of contemporary culture. His work analyses topics such as the relation between art and politics, the problematics of poststructuralist and feminist approaches to art, the re-emergence and relevance of theories of the sublime, and the continuing possibilities of artistic creativity. The central theme of the book is that there are constants in human experience around which art and philosophy constellate. At the same time, however, due account must be given of the ways in which such constants are historically mediated. By articulating various aspects of this relation, Crowther shows that the postmodern sensibility can be more than that of an alienated consumerism. Understood in the proper theoretical context, it is grounded on experience and artefacts which humanize.